Receipt of rental payment for the use of natural budgets in the local budget in the context of modernizing the economic mechanism of natural use - N. Medynska; Y. Moroz (Zemleustrìj, Kadastr ì Monìtorìng Zemelʹ, 2023)
It is substantiated that the necessary institutional prerequisite for increasing the effectiveness of extended reproduction and economic development of natural resource potential is the modernization of the economic mechanism of nature use both at the national, regional and local levels, in particular in the part of the transformation of the system of fiscal regulation of the use of subsoil for the extraction of minerals. Studies have shown that the deepening of budget-fiscal decentralization requires more effective use of endogenous factors of socio-economic development of territorial communities, in the spectrum of which the increase in the effectiveness of fiscal regulation of subsoil use through the improvement of the methodology of extraction and distribution of rent for the use of subsoil is of particular importance. It was established that in the years 2007-2021, several phases of growth and decline are observed in the dynamics of rent payments for the use of subsoil to the local budgets of Ukraine, which correlates with the dynamics of socio-economic uplift, the impact of the global financial crisis on the national economy, changes in the percentages of deduction of mineral and raw materials rents to public financial funds of the respective territories. It has been proven that in the conditions of budgetary and fiscal decentralization, favorable conditions have been formed for increasing the share of rent deductions for subsoil use to local budgets, which will make it possible to form special financial funds for the reproduction of mineral and raw material potential and increase the interest of local self-government in its complex use. It is substantiated that the revision of the principles of subsoil use rents should be preceded by the modernization of the economic mechanism of nature use in terms of the diversification of payments for the extraction of minerals, and this will make it possible to ensure the equivalence of the extraction of mineral and raw material rents and its adequate distribution between public budgets of different taxonomic levels . Key words: economic mechanism of nature use, mineral and raw material rent, rent for subsoil use, local budgets, minerals, territorial community.